2015
DOI: 10.1590/1807-1929/agriambi.v19n4p317-323
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de capim Tifton 85 sob irrigação e doses de nitrogênio

Abstract: O trabalho foi conduzido em uma propriedade de atividade leiteirana município de Xambrê, região Noroeste do Paraná, no período de março de 2011 a fevereiro de 2012 com o objetivo de avaliar a produtividade e a composição botânica do capim Tifton 85 com e sem irrigação sob doses de nitrogênio. As parcelas experimentais foram implantadas com delineamento de blocos ao acaso com e sem irrigação e as subparcelas por meio de quatro doses de nitrogênio: 0, 20, 40 e 60 kg ha-1 ciclo de pastejo-1, com quatro repetições… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 16 publications
2
14
0
14
Order By: Relevance
“…Possibly, in this situation the plant did not have available a suitable combination of water, nitrogen and potassium needed for full development. According to GOMES et al(2015), working with Tifton 85, the grass productivity generally responds linearly to nitrogen fertilization, while the water tension in the soil was kept below 35 kPa.…”
Section: Wlmentioning
confidence: 99%
“…Possibly, in this situation the plant did not have available a suitable combination of water, nitrogen and potassium needed for full development. According to GOMES et al(2015), working with Tifton 85, the grass productivity generally responds linearly to nitrogen fertilization, while the water tension in the soil was kept below 35 kPa.…”
Section: Wlmentioning
confidence: 99%
“…The productive increment in irrigated pastures, compared with rainfed cultivation, is evidenced by many authors (Müller et al, 2002;Gomes et al, 2015;Sanches et al, 2015). Research results have demonstrated the possibility of maintaining, in irrigated pastures during the dry period, 40 to 50% of the animal stocking rate that is maintained in the spring/summer, while these values comprehend only 10 to 20% in the absence of irrigation (Alvares, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Tifton 85 proporcionou maior produção de matéria seca. Gomes et al (2015) observaram que a irrigação promove maior produtividade de matéria seca de Capim Tifton 85, tanto na safra como na entressafra.…”
Section: Resultados E Discussõesunclassified
“…No entanto deve-se buscar estratégias ideais de manejo para otimizar o uso da água, devido conflitos de interesse pelo seu uso, como o consumo humano (FAGGION et al, 2009) Diversos trabalhos observaram que a produção de gramíneas são influenciadas pela disponibilidade de água. Entre os trabalhos podemos destacar os de Teodoro et al (2002) trabalhando com Capim Tanzânia (Panicum maximum), Marcelino et al (2003) e Gomes et al (2015) A escolha da gramínea é outro fator determinante na produção de pastagens. Entre as novas alternativas, a Brachiaria brizantha cv.…”
Section: Introductionunclassified